Rain attenuation models at ka band for selected stations in the southwestern region of Nigeria - Abayomi Isiaka Yussuff; George Tavwo; Nor Hisham Haji Khamis (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Rain is the major factor in radio propagation analyses that is responsible for outage on terrestrial point-to-point and point-to-multipoint radio communication systems at millimeter wave bands. This hampers radio wave signal transmission in the tropics. This paper investigates the performance of ITU-R P.530-16, Silver Mello, Moupfouma and Abdulrahman rain attenuation prediction models using locally-sourced data. The aim is to determine their suitability or otherwise in tropical Nigeria. Two years daily rainfall data were sourced from the Nigerian Meteorological Services (NIMET) for six different stations in southwestern Nigeria. Southern Nigeria is predominantly influenced by the southwest monsoon wind from the Atlantic Ocean due to its proximity to the coastal belt. The data were analyzed using these prediction models by comparing with measured data. The ITU-R P.530-16 rain attenuation prediction model closely matched the measurement value for p≥0.1% of the time but over-estimated it at p<0.1% while Abdulrahman and Silver Mello proposed prediction models generally over-estimated for p<0.01 of time exceeded. Overall, Abdulrahman proposed prediction model presented the best performances; it was closely followed by Silver Mello, ITU-R and Moupfouma prediction models respectively. These results further accentuate the need for urgent review of the ITU-R P.530-16 prediction model or alternatively, the development of a separate rain attenuation prediction model specifically for the stations in the tropical region.